Capacitively coupled radio-frequency discharges in nitrogen at low pressures - Alves, L. L. (2012)
This paper uses experiments and modelling to study capacitively coupled radio-frequency (rf) discharges in pure nitrogen, at 13.56MHz frequency, 0.1–1 mbar pressures and 2–30W coupled powers. Experiments performed on two similar (not twin) setups, existing in the LATMOS and the GREMI laboratories, include electrical and optical emission spectroscopy (OES) measurements. Electrical measurements give the rf-applied and the direct-current-self-bias voltages, the effective power coupled to the plasma and the average electron density. OES diagnostics measure the intensities of radiative transitions with the nitrogen second-positive and first-negative systems, and with the 811.5 nm atomic line of argon (present as an actinometer). Simulations use a hybrid code that couples a two-dimensional time-dependent fluid module, describing the dynamics of the charged particles (electrons and positive ions N+2 and N+4 ), and a zero-dimensional kinetic module, describing the production and destruction of nitrogen (atomic and molecular) neutral species. The coupling between these modules adopts the local mean energy approximation to define space–time-dependent electron parameters for the fluid module and to work out space–time-averaged rates for the kinetic module. The model gives general good predictions for the self-bias voltage and for the intensities of radiative transitions (both average and spatially resolved), underestimating the electron density by a factor of 3–4.